A competência social do psicólogo: estudo com profissionais de instituições no atendimento às famílias que vivem em situação de vulnerabilidade social - Lima, Maria José (2010)
Aiming to develop an analysis of psychologists perception about their competence working in institutions that serve the population living in social vulnerability, this research has turned to this context, exploiting the developed resources, facilitating and complicating factors and the comprehension that these professionals have of their own action, considering the facets of psychotherapy and social. Qualitative research-level exploratory and descriptive, made use of a questionnaire of the participant and the Technical Focus Group. The participants were psychologists working in institutions that serve the population living in socially vulnerable in São José dos Campos / São Paulo. The analysis of material obtained in the group was based on some tools of qualitative method of content analysis. For the interpretation phase, we used the theoretical contributions of systems thinking new paradigm. The results point to the perception of a place under construction, the institutional psychologist in search of identity and enhancement, as well as the need of building skills to work in that context. Participants perceive their actions as nonclinical and seek their place in society, given the current demands for greater involvement in contexts of vulnerability